Investigation of the Omaha System for Dentistry - Jurkovich, M.W.; Ophaug, M.; Salberg, S.; Monsen, K. (Applied Clinical Informatics, 2014)
Objective: Today, dentists and hygienists have inadequate tools to identify contributing factors to dental disease, diagnosis of disease or to document outcomes in a standardized and machine readable format. Increasing demand to find the most effective care methodologies make the development of further terminologies for dentistry more urgent. Preventive care is the focus of early efforts to define best practices. We reviewed one possibility with a history of public health documentation that might assist in these early efforts at identifying best practices.Methods: This paper examines, through a survey of dentists, the Omaha System Problem Classification Scheme. The survey requested that dentists rate the usefulness of knowing about specific signs and symptoms for each of the 42 problems within the Problem list of the Omaha System. Results: Using a weighted scoring system, 22 of the 42 problems received over 50% of the possible maximum score and 30 of the 42 problems received at least 25% of the possible points. Conclusion: These findings suggests that further evaluation of The Omaha System, may be useful to dentistry. At a minimum, the survey provides additional information about non-physiological problems, signs, and symptoms that may be appropriate for documentation purposes within an electronic health record (EHR) used in dentistry.Citation: Jurkovich MW, Ophaug M, Salberg S, Monsen K. Investigation of the Omaha System for Dentistry. Appl Clin Inf 2014; 5: 491–502 http://dx.doi.org/10.4338/ACI-2014-01-RA-0001
Keywords: Omaha system; dentistry; electronic health records; problem classification; SNOMED CT